The beneficial effects of thymoquinone on viability and differentiation of human adipose tissue-derived mesenchymal stem cells - Ahsen Erginsoy; Nur Seda Gokdemir; Venhar Cinar; Eda Koseoglu; Zeynep Burcin Gonen; Tuba Dilay Kokenek Unal (Medicine Science)
Thymoquinone is the primary active substance extracted from Nigella sativa. It has been reported to have many beneficial and protective effects on several cell types. However, there are limited studies about its effects on mesenchymal stem cells (MSCs). The purpose of this study is to investigate the effect of thymoquinone on the cell viability, proliferation, and differentiation of MSCs obtained from human adipose tissue. MSCs were obtained from the biobank and treated with concentrations of 50 nM, 100 nM, 200 nM, and 300 nM thymoquinone. Cell viability, proliferation, and apoptosis analysis were performed. The effects of thymoquinone on the differentiation of human adipose tissue-derived mesenchymal stem cells (haMSCs) were investigated through adipogenic, osteogenic, and chondrogenic assays. As a result of our study, doses of 50 nM, 100 nM, 200 nM, and 300 nM thymoquinone have been demonstrated to enhance cell proliferation, prevent apoptosis, and contribute to adipogenic, chondrogenic, and osteogenic differentiation. Thymoquinone promotes the viability of haMSCs and induces differentiation into osteogenic, adipogenic, and chondrogenic lienages. Therefore, it is an auxiliary active ingredient that can be used safely in regenerative medicine. [Med-Science 2024; 13(4.000): 973-8]